A CORRELATION BETWEEN THE KAPPA NUMBER AND THE VENTORIM INDEX IN THE BLEACHING PROCESS - Vitor Hideyoshi Hayashida Ribeiro; Evelyn Eduarda Gil dos Santos; Fabiana Clara Cezar Alves; Marianne Vitória Gil dos Santos; Higor Rogério Favarim; Gustavo Ventorim (Revista Árvore)
ABSTRACT The determination of the kappa number in the bleaching process is typically conducted with a pulp quantity between 3 and 4 grams, allowing for the calculation of values above four. However, after the oxidative extraction stage with hydrogen peroxide, the pulp presents a kappa number lower than this value. Therefore, the present study proposes a new method for determining the kappa number by creating the Ventorim bleaching index, which avoids the inconveniences associated with traditional kappa number analysis. For this study, industrial oxygen-delignified pulp was used. Four different ECF bleaching sequences were performed: OD(E+P)DD, OAD(E+P)DP, OADEDP, and OAEDP, along with the determination of the kappa number and the Ventorim bleaching index. The Ventorim index was based on the four chlorinefree bleaching sequences (ECF), all of which achieved a final brightness of 90% ISO, with very similar R2 values and linear regressions. Consequently, a single equation was generated using all the data: Y=0.7202x+0.1464. This unified approach simplifies the analysis and broadens the applicability of the Ventorim bleaching index in the pulp and paper industry.